Investigation of Isolated Human Heart by Micro-Computed Tomography - Caesa PMF., et al (Faculty of Medicine, Public Health and Nursing Universitas Gadjah Mada, 2017)
Investigation of Isolated Human Heart by Micro-Computed Tomography